GUILLAIN-BARRE SYNDROME COMPLICATING DENGUE FEVER - Gitte, Sachin; G, Pradhan; M, Santoshi; M, Sudheer (International Journal of Clinical and Biomedical Research, 2018)
Guillain-Barre syndrome (GBS) is an immune mediated demyelinating polyradiculo-neuropathy manifesting as ascending paralysis with loss of deep tendon reflexe. It has been seen more commonly as a post infectious complication of Campylobacter jejuni and Cytomegalovirus infection but a rare neurological manifestation of Dengue infection. Here we are presenting such a case of Guillain-Barre syndrome as a complication of Dengue infection